PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN TOKO BANGUNAN DI SANGATTA-KUTAI TIMUR - Meita Sondang Rizki (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2017)
The study tries to identify to what extent service quality  for satisfaction of  consumen store building  in Sangatta.  Analysis model used to prove hypothesis is model analysis multiple linier regression that be analysed with using statistics computer program package, that is SPSS v. 20.0 for Windows. Furthermore it was conducted examination for validity of data by multikolinieritas test, heteroskedastisitas test and autocorrelation test. Result of statistics analysis show that coefficient of the free variables regression, that is involvement  factor in tangibles  (X1) =  0,161, reliability   (X2) = 0,088, responsiveness (X3) = 0,168,  assurance  (X4) = 0,194, emphaty (X5) = 0,122 and constanta equal  to 0,541. Equation  of multiple linier regression is: Y =  0,541 + 0,161 X1 + 0,088 X2 + 0,168 X3 + 0,194 X4 + 0,122 X5 + e            Conclusion that receive that level of influence explained by tangibles, reliability, responsiveness, assurance, emphaty  are as independent variable impact toward satisfaction  of consumen store building equal to correlation  coefficient (R), that is 0,860  and level of depended  performance to second of  free variables above is equal to determination  coefficient value (R2) that is 0,740 or 74,0 %.  Result of analysis F – test  indicate that all free variables by together have significant influence toward satisfaction of consumen store building in Sangatta. By partial, variable  tangibles, responsiveness, assurance, emphaty  have  significant  influence to satisfaction  of  consumen store building in Sangatta. Variabel independent  has dominant influence to satisfaction  of    consumen store is tangibles.